Clay cooling pots technologies for storage of Fuzzy Bomb and Bonita Roma varieties of tomato fruits - Nasiru Alhassan, Tabormah Charles, Dakorah Albert, Addae Kwasi Charles, Aziz Mohazo, Iddri, Adams Abdul-Rahaman (Journal of Aridland Agriculture, 2015)
Tomato fruits are perishable vegetables that usually deteriorate faster due to insufficient postharvest technologies at the various stages which include harvesting, pre-cooling, packaging, and transportation during marketing and storage. The objective of this research was to evaluate the quality of tomato fruits using single wall and double wall clay pots for storage. Two varieties of mature tomato fruits were purchased from a commercial farmer in the Upper West Region of Ghana in Wa Municipality. A total of 90 fruits without any damage and decay were used for the experiment. The entire sample fruits were divided into three to represent the various treatments. Data were subjected to analysis of variance using Mintab version 16. The two-way ANOVA was used for weight loss and color changes. The general linear model was used for sensory evaluation. On day 10 of the experimental period, the results obtained from weight losses indicated that there was upward increase in weight loss on double wall Bonita Roma with 13.1% compared to Fuzzy Bomb with 9.6%. Based on the results generated on the percentage weight in single wall, Bonita Roma increased to 24.6% compared with Fuzzy Bomb with 15.8%. Eventually, it was clearly indicated that control Fuzzy Bomb recorded the highest average weight loss of 23.5% compared with Bonita Roma with 15.3%. On day 10, the results on color changes indicated that fruits stored in double wall clay pots for Fuzzy Bomb and Bonita Roma were 3.9 and 3.5, respectively, on the average. Furthermore, the comparison of color of fruits in the single wall clay pot for Fuzzy Bomb recorded 3.9 as compared to 3.6 for Bonita Roma . Then, the control Bonita Roma was 3.6 compared to Fuzzy Bomb at 3.8. The overall acceptance for single wall Fuzzy Bomb recorded 21 and Bonita Roma recorded 20.8. Eventually, it was clearly demonstrated that Fuzzy Bomb variety stored in double wall clay pot performed better when compared to Bonita Roma while Bonita Roma stored in single wall clay pot resulted in better storage compared with Fuzzy Bomb variety.